Salinity of our oceans can help us predict the effects of climate change - Azizul Helmi, Sofian (2021)
Floods have lately wreaked havoc across Europe, while the Chinese city of Zhengzhou received the equivalent of a year’s worth of rain in just three days. In contrast, high temperatures and droughts in northwest America and Turkey have sparked wildfires and killed hundreds of people. How about Malaysia during the monsoon season, especially in the east coast region?